Methodological principles and stages of competitive processes of stabilization of existing moving objects - Блохін, Л.М.; Кривоносенко, О.П.; Осадчий, С.І. (Proceedings of National Aviation University (archive), 2009)
Advanced methodological fundamentals of the optimal stabilization system’s development for the real moving vehicles based on their prototypes testing are proposed. The stochastic statements of used modern technologies of native methods of optimal stabilization of objects and structural identification dynamics models of the real system’s parts, and also auctioning influences in the stabilization object’s systems, which are moderation, have to guarantee the competitiveness of their stabilization processes in corresponding modes of motion.